A Method for Ancient Book Named Entity Recognition Based on BERT-Global Pointer - Jiang, Wen (International Journal of Computer Science and Information Technology, 2024)
Correct identification of entities in ancient books and documents is the basic step of analyzing ancient Chinese texts, and provides an important prerequisite for in-depth mining of humanistic knowledge in ancient books and documents. In CCL2023 named entity recognition task of ancient books, according to the task definition and the re-quirements of the task organizer, this paper proposes the BERT Global Pointer named entity recognition model; Fine tune the field adaptation training based on the unlabeled 24 history ancient book text data; SWA, FGM, cross validation and post-processing are used to improve the recognition accuracy of the model. The experimental results show that the model and the strategy proposed in this paper have good recognition effect in the multi dynasties, cross domain ancient book entity recognition scene. F1 value on the final line reaches 95.083%.